2020
DOI: 10.31186/j.agroindustri.10.1.12-20
|View full text |Cite
|
Sign up to set email alerts
|

STUDY ON POTENTIALS OF PINEAPPLE SKIN EXTRACT FERMENTED WITH Lactobacillus casei AS A PROBIOTIC BEVERAGE BY IN VIVO

Abstract: The objectives of the research are to learn the effect of fermented drink of pineapple peel extract fermented by Lactobacillus casei toward microflora of digest of Sprague Dawley rats and to know its potential as a probiotic drink.  The treatment compiled by Randomized Complete Block Design (RCBD) with six repetitions.  Eighteen male weanlings Sprague Dawley rats are divided into three groups.  Each group consists of six rats and has different treatments.  One group was given a lactate fermented beverage of pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…According to Moslehishad et al [25] proteolytic activity in the probiotic bacteria is the key determinant affecting total acid of the drink. Rizal et al [17] reported that L. casei might ferment 90% of glucose into lactic acid, meanwhile B.longum only 60% of it [26]. Similar experiment at previous study [27], total acid in the product were between 0.40% -0.57%.…”
Section: Characteristics Of Whey Probiotic Drink Acidity Value and To...supporting
confidence: 71%
See 1 more Smart Citation
“…According to Moslehishad et al [25] proteolytic activity in the probiotic bacteria is the key determinant affecting total acid of the drink. Rizal et al [17] reported that L. casei might ferment 90% of glucose into lactic acid, meanwhile B.longum only 60% of it [26]. Similar experiment at previous study [27], total acid in the product were between 0.40% -0.57%.…”
Section: Characteristics Of Whey Probiotic Drink Acidity Value and To...supporting
confidence: 71%
“…Mother culture preparation was carried out based on Rizal et al [17] with some modifications. Total bacteria was analyzed based on the resulted culture.…”
Section: Culture Preparationsmentioning
confidence: 99%